Invisible man eaudiobook A father brown mystery. - Chesterton, G.K (christianaudio, 2011)
Listeners will delight in these masterful chronicles of the adventures and mishaps of Father Brown. Small, round-faced and engagingly innocent, Brown is a Roman Catholic priest from East Anglia. He also happens to be a top-notch detective, possessing that rarest of all gifts - an intuition that never fails.